Rigid and Flexible Docking Study with ADME Evaluation of Hesperetin Analogues as LecB Inhibitors in Pseudomonas aeruginosa - Arfan, Arfan; Rayani, Nur; Ruslin, Ruslin; Kasmawati, Henny; Aman, La Ode; Asnawi, Aiyi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Infections caused by Pseudomonas aeruginosa pose a considerable challenge in terms of treatment. The bacterium's key virulence factor, particularly LecB, plays a significant role in bacterial adherence, infections, biofilm formation, and suppression of the host immune response. This study aims to assess the affinity and interactions of hesperetin analogs against LecB in P. aeruginosa. The investigation utilized the molecular docking method, employing a combination of rigid and flexible docking. The docking results successfully identified hesperetin 7-O-glucoside and hesperetin 7-O-rhamnoside, demonstrating superior binding energies compared to MJO as the reference ligand. Rigid docking indicated binding energies of -7.0 and -7.2 kcal/mol for hesperetin 7-O-glucoside and hesperetin 7-O-rhamnoside, respectively. Subsequently, flexible docking revealed lower binding energies for both compounds, reaching -10.3 kcal/mol. These top-performing compounds exhibited interactions with critical residues, including Asn70, Arg72, Thr98, Asp99, Asp96, Asn21, and Ser23, strategically positioned in LecB's substrate-binding site in P. aeruginosa. Notably, hesperetin 7-O-rhamnoside displayed an excellent ADME profile and a favorable safety profile, as it was predicted not to inhibit CYP enzymes. The hesperetin analog also met Lipinski's rules, suggesting its suitability as an oral drug. In conclusion, this research unveils the potential antibacterial activity of hesperetin analogs and provides an opportunity for experimental verification of these compounds as candidates for antibacterial drugs against P. aeruginosa.